Proposta de implantação de pequena empresa têxtil a partir de produtos reciclados de pet no município de Franca – SP - REZENDE, Michele Pereira de (109, 2014)
REZENDE, Michele Pereira de. Proposta de implantação de pequena empresa têxtil a partir de produtos reciclados de pet no município de Franca – SP. 2014. Trabalho de Graduação (Curso Superior em Gestão da produção Industrial). Faculdade de tecnologia " Dr. Thomaz Novelinho”, Franca, 2014.

This paper aims at proposing the deployment of a small company in Franca, SP, presenting the panorama of textile manufacturing in this city, which has experienced great expansion in recent years. The methods employed in this study were bibliographic surveys and case study, presenting recycling and characteristics of Polyethylene Terephthalate (PET) and the production process of the fabric from the PET bottle by means of quali-quantitative analysis. Ways of how environmental management and reverse logistics can be potential tools for increased productivity and profitability in a corporation are presented. Therefore,the proposal of deployment of a small manufacturer of tissue from PET to the region of Franca, SPwill be demonstrated. A simulation of business model, using CANVAS, will show that the company aims at meeting the customers’ needs in a sustainable, social and economic way.
Proposal for the implementation of a small textile company from recycled pet products in the municipality of Franca – SP
Keywords: Logística reversa; Reciclagem; Indústria têxtil; Controle e Processos Industriais